Effect of Seaweed Rice Intervention on Fasting Blood Glucose Levels and Antioxidant Activity in Prediabetics and Diabetics Adults - Mustika, Gina; Damayanthi, Evy; Purwaningsih, Sri (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to analyze the effect of seaweed rice on Fasting Blood Glucose (FBG) and Superoxide Dismutase (SOD) levels in humans measured using finger prick method. This research was a quasi-experimental study with pre-posttest design. A total of 34 adult subjects were divided into control and intervention groups. The intervention group received 250 g/day of seaweed rice made by extrusion method at 8 AM for 42 days, while the control group received none. The results showed that the intervention had no significant effect on either FBG or SOD levels.